2018
DOI: 10.3126/nmcj.v20i4.25140
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and Health Status Assessment of Geriatric People of One Rural District in Nepal

Abstract: Aging is an inevitable process, old age cannot be healed. It can only be protected, promoted and extended by adding quality to life. To explore the health and nutrition status of geriatric people that need to be accommodated in future priority health programme of Nepal this cross sectional study was done in two selected rural VDCs of Rupandehi District of Nepal. In this study out of a total of participants (n=364) 9.0% were severely underweight, 15.5% were underweight and 24.5% were malnourished. Three hundred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 5 publications
(6 reference statements)
0
10
0
Order By: Relevance
“…More recently, young couples in Nepal have been seeking employment and education away from their families, often in cities (CBS Nepal 2019). Since city living is expensive, people are having smaller families, and supporting older parents is becoming less of a priority for many (Shrestha 2012). In addition to a changing family structure, migration has directly affected older family members (Limbu 2012), as members of the traditional family unit are no longer close by to care.…”
Section: Study Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, young couples in Nepal have been seeking employment and education away from their families, often in cities (CBS Nepal 2019). Since city living is expensive, people are having smaller families, and supporting older parents is becoming less of a priority for many (Shrestha 2012). In addition to a changing family structure, migration has directly affected older family members (Limbu 2012), as members of the traditional family unit are no longer close by to care.…”
Section: Study Contextmentioning
confidence: 99%
“…Researchers have studied the relationship between children's migration and left-behind older parents’ physical health (Lu 2012; Evandrou et al 2017), mental health (Song 2017; Wang et al 2017; Inoue et al 2019; Mergo 2020), quality of life (Liang and Wu 2014; Ye, Chen and Peng 2017) and overall well-being (Gassmann et al 2012; Silverstein, Cong and Li 2006). Generally, research on left-behind parents’ mental health has reported increased depression (Cheng et al 2015; Song 2017; Wang et al 2017; Zhai et al 2015), loneliness (Cheng et al 2015; Liu and Guo 2007; Wang et al 2017), anxiety (Wang et al 2013; Arenas and Yahirun 2010), and poorer cognitive ability (Zhai et al 2015) among older parents with migrant children.…”
Section: Introductionmentioning
confidence: 99%
“…The absolute number of people aged 60 years and above is expected to increase from 605 million to 2 billion over the same period (WHO, 2012). In Nepal, the trend has been the same; there were 1.5 million elderly inhabitants in 2001 and 2.1 million elderly inhabitants in 2011 that constituted 6.5 percent and 8.14 percent, respectively, of the country's total population in these 2 years (Shrestha, 2012). During the year 1991-2001, the annual elderly population growth rate of Nepal was 3.39 percent which is higher than an annual population growth rate of 2.3 percent (CBS, 2011).…”
Section: Introductionmentioning
confidence: 96%
“…1.5 million (6.5%) in 2001 which increased to 2.5 million (8.1%) in 2011. 6 With the increase in longevity, the likelihood of experiencing more non-communicable chronic conditions also increases. 7 - 9 The impact of multimorbidity is greater than the cumulative effect of the single condition.…”
Section: Introductionmentioning
confidence: 99%